Optimizing the Psychosocial Function Measures in the International Consortium for Health Outcomes Measurement Standard Set for Cleft. Issue 2 (10th November 2022) - Apon, Inge; van Leeuwen, Nikki; Koudstaal, Maarten J.; Allori, Alexander C.; Rogers-Vizena, Carolyn R.; Wolvius, Eppo B.; Klassen, Anne F.; Versnel, Sarah L.
Abstract : Background: To ensure the feasibility of implementing PROMs in clinical practice, they must be continually appraised for undue burden placed on patients and clinicians and their usefulness for decision-making. This study assesses correlations between the CLEFT-Q psychosocial scales in the International Consortium for Health Outcomes Measurement Standard Set for cleft and explores their associations with patient characteristics and psychosocial care referral. Methods: Spearman correlation coefficients were calculated for CLEFT-Q psychological function, social function, school function, face, speech function, and speech-related distress scales. Logistic regressions were used to assess the association of cleft phenotype, syndrome, sex, and adoption status on scale scores and clinical referral to psychosocial care for further evaluation and management. Results: Data were obtained from 3067 patients with cleft lip and/or palate at three centers. Strong correlations were observed between social function and psychological function ( r > 0.69) and school function ( r > 0.78) scales. Correlation between school function and psychological function scales was lower ( r = 0.59 to 0.68). Genetic syndrome (OR, 2.37; 95% CI, 1.04 to 5.41), psychological function (OR, 0.92; 95% CI, 0.88 to 0.97), school function (OR, 0.94; 95% CI, 0.90 to 0.98), and face (OR, 0.96; 95% CI, 0.94 to 0.98) were significant predictors for referral to psychosocial care. Conclusions: Because social function as measured by the CLEFT-Q showed strong correlations with both school and psychological function, its additional value for measuring psychosocial function within the Standard Set is limited, and it is reasonable to consider removing this scale from the International Consortium for Health Outcomes Measurement Standard Set for cleft.